2018
DOI: 10.1111/ppl.12823
|View full text |Cite
|
Sign up to set email alerts
|

Control of adventitious root formation: insights into synergistic and antagonistic hormonal interactions

Abstract: Plants have evolved sophisticated root systems that help them to cope with harsh environmental conditions. They are typically composed of a primary root and lateral roots (LRs), but may also include adventitious roots (ARs). Unlike LRs, ARs may be initiated not only from pericycle cells, but from various cell types and tissues depending on the species. Phytohormones, together with many other internal and external stimuli, coordinate and guide every step of AR formation from the first event of cell reprogrammin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
147
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 74 publications
1
147
0
Order By: Relevance
“…Both pathways act synergistically in control of the JA response, as 335 indicated by the much lower numbers of ARs produced by ninjamyc2-322B double mutants 336 than the parental lines (ninja and myc2-322B) and wild-type controls. Therefore, the strong 337 phenotype of ninjamyc2-322B double mutants may be due to de-repression of not only MYC2, 338 and model systems (Lakehal and Bellini, 2018). In this study, we genetically demonstrated that 358 depleting CKs by either blocking their biosynthesis or enhancing their degradation restores the 359 ARI wild-type phenotype in an ERF115-overexpressing line, confirming that ERF115 represses 360 ARI through CK signaling.…”
supporting
confidence: 56%
“…Both pathways act synergistically in control of the JA response, as 335 indicated by the much lower numbers of ARs produced by ninjamyc2-322B double mutants 336 than the parental lines (ninja and myc2-322B) and wild-type controls. Therefore, the strong 337 phenotype of ninjamyc2-322B double mutants may be due to de-repression of not only MYC2, 338 and model systems (Lakehal and Bellini, 2018). In this study, we genetically demonstrated that 358 depleting CKs by either blocking their biosynthesis or enhancing their degradation restores the 359 ARI wild-type phenotype in an ERF115-overexpressing line, confirming that ERF115 represses 360 ARI through CK signaling.…”
supporting
confidence: 56%
“…It is well known that auxin can stimulate adventitious rooting in several plant species 308 (Lakehal & Bellini, 2019), therefore we tested whether different types of auxin could 309 stimulate ARI under cWL. Three-week-old de-rooted seedlings were treated with 1 or 310 5 µM of Indole 3-Acetic Acid (IAA), 1-Naphthalene 3-Acetic Acid (1-NAA) or Indole 1B-D).…”
Section: Hormone Profiling Experiments 249mentioning
confidence: 99%
“…Although this requires effective rooting of stem cuttings, this is often not achieved and many studies conducted at physiological, biochemical and molecular levels to better understand the entire process have shown that AR formation is a heritable quantitative genetic trait controlled by multiple endogenous and environmental factors. In particular, it has been shown to be controlled by complex hormone cross-talks, in which auxin plays a central role (36,37). The specificity of auxin response is thought to depend on a specific combinatorial suite of ARF-Aux/IAA protein-protein interactions from among the huge number of potential interactions that modulate the auxin response of gene promoters via different affinities and activities (reviewed in (3,6)).…”
Section: Discussionmentioning
confidence: 99%